2022
DOI: 10.1080/20008198.2022.2055890
|View full text |Cite
|
Sign up to set email alerts
|

Online training for evidence-based child trauma treatment: evaluation of the German language TF-CBT-Web

Abstract: Background Evidence-based trauma-focused interventions for treating PTSD in children and youth are barely used in practice. Web-based training has proven to be an effective way of transferring knowledge to healthcare professionals. Objective TF-CBT Web is a web-based training programme designed to foster the dissemination of Trauma Focused Cognitive Behavioural Therapy (TF-CBT) for children and youth, and is run by the Medical University of South Carolina. This paper de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Specific knowledge about trauma, its consequences, and evidence-based treatment is required (Cook et al, 2019 ; Schäfer et al, 2018 ), and therefore these skills should be acquired via specialised training. Previous research showed that clinicians with more than 10 years of work experience were less likely to complete Trauma-Focused – Cognitive Behavioural Therapy online training programme, compared to users with less than five years of work experience (Kasparik et al, 2022 ). Therefore, it is crucial to inform professionals that even experienced clinicians may significantly benefit from post-diploma training, and it is essential to regularly improve specific trauma care competencies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specific knowledge about trauma, its consequences, and evidence-based treatment is required (Cook et al, 2019 ; Schäfer et al, 2018 ), and therefore these skills should be acquired via specialised training. Previous research showed that clinicians with more than 10 years of work experience were less likely to complete Trauma-Focused – Cognitive Behavioural Therapy online training programme, compared to users with less than five years of work experience (Kasparik et al, 2022 ). Therefore, it is crucial to inform professionals that even experienced clinicians may significantly benefit from post-diploma training, and it is essential to regularly improve specific trauma care competencies.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we only investigated participants’ confidence in their trauma care competencies in the current study. Although feeling confident in one’s abilities is an important factor leading to a sense of control in terms of the ability to change behaviour (Albright et al, 2016 ; Kasparik et al, 2022 ) and is associated with treatment outcomes (Espeleta et al, 2022 ), it would be very useful to evaluate the effectiveness of training using additional methods, such as how it transfers into actual clinical practice and treatment outcomes (Cook et al, 2019 ). The inclusion of various other less subjective study outcomes, for example, knowledge questionnaires, case formulation examples, treatment plan outlines, evaluations of clinical performance by experienced clinicians in case analysis and supervision, and the use of patient data could provide a broader picture of the outcomes of training programs.…”
Section: Discussionmentioning
confidence: 99%